Nasal Intermittent Positive Pressure Ventilation versus Continuous Positive Airway Pressure and Apnea of Prematurity: A Systematic Review and Meta-Analysis - Sabsabi, Bayane; Harrison, Ava; Banfield, Laura; Mukerji, Amit (American Journal of Perinatology, 2021)
Objective The study aimed to systematically review and analyze the impact of nasal intermittent positive pressure ventilation (NIPPV) versus continuous positive airway pressure (CPAP) on apnea of prematurity (AOP) in preterm neonates.Study Design In this systematic review and meta-analysis, experimental studies enrolling preterm infants comparing NIPPV (synchronized, nonsynchronized, and bi-level) and CPAP (all types) were searched in multiple databases and screened for the assessment of AOP. Primary outcome was AOP frequency per hour (as defined by authors of included studies).Results Out of 4,980 articles identified, 18 studies were included with eight studies contributing to the primary outcome. All studies had a high risk of bias, with significant heterogeneity in definition and measurement of AOP. There was no difference in AOPs per hour between NIPPV versus CPAP (weighted mean difference = −0.19; 95% confidence interval [CI]: −0.76 to 0.37; eight studies, 456 patients). However, in a post hoc analysis evaluating the presence of any AOP (over varying time periods), the pooled odds ratio (OR) was lower with NIPPV (OR: 0.46; 95% CI: 0.32–0.67; 10 studies, 872 patients).Conclusion NIPPV was not associated with decrease in AOP frequency, although demonstrated lower odds of developing any AOP. However, definite recommendations cannot be made based on the quality of the published evidence.Key Points
Keywords: continuous positive airway pressure; nasal intermittent positive pressure ventilation; preterm; neonates; noninvasive respiratory support